Middle Miocene high-resolution calcareous plankton biostratigraphy at Site 926 (Leg 154, equatorial Atlantic Ocean): paleoecological and paleobiogeographical implications - TURCO, E.; BAMBINI, A. M.; FORESI, L. M.; IACCARINO, S.; LIRER, F.; MAZZEI, R.; SALVATORINI, G. (Geobios, 2002)
High-resolution calcareous plankton (planktonic foraminifera and calcareous nannofossils) biostratigraphy is presented from the Middle to early Late Miocene interval (from 14.45 to 8.86 Ma) at Site 926 (ODP Leg 154, equatorial Atlantic Ocean). The main bioevents used in the low-latitude zonal schemes, and also auxiliary events revealing potential biostratigraphic value have been recognised. The investigated succession ranges from N.10 to N.16 Zones based on planktonic foraminifera, and from NN5 (CN4) to NN10 (CN8) Zones based on calcareous nannofossils. The evolution of the planktonic foraminiferal Globorotalia fohsi lineage appears to be environmentally controlled. The main diagnostic features of the species of this lineage are not always evident, rendering problematic the definition of the N.9/N.10, N.10/N.11 and N.11/N.12 zonal boundaries. Calcareous plankton events have been calibrated on the basis of the Astronomical Time Scale of Shackleton and Crowhurst [Shackleton, N.J., Crowhurst, S., 1997. Sediment fluxes based on an orbitally tuned time scale 5 Ma to 14 Ma, Site 926. In: Curry, W. B., Shackleton, N.J., Richter, C., Bralower, T.J. (Eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program) 154, pp. 69-82]. The astrobiochronology obtained at Site 926 has been compared with that of the Mediterranean astronomically calibrated deep marine successions, allowing the evaluation of the degree of synchroneity and diachroneity of bioevents. Some bioevents, such as the last occurrence of Globigerinoides subquadratus dated at 11.55 Ma, the last occurrence of Sphenolithus heteromorphus dated at 13.51 Ma and the last common occurrence of Cyclicargolithus floridanus calibrated at 13.32 Ma, are near-synchronous events between the equatorial Atlantic and the Mediterranean area indicating their high biostratigratigraphic value in global correlation. The diachroneity of the last occurrence of Paragloborotalia siakensis, the first occurrence of Neogloboquadrina ...